The man [videorecording (DVD)] - Mayfield, Les; Jackson, Samuel L.; Levy, Eugene, 1946- (New Line Home Entertainment : Distributed by Warner Home Video, 2006)
ATF agent Derrick Vann's partner, who happened to be corrupt, has been killed after a cache of guns were stolen from the ATF office in Detroit. Internal affairs believe Derrick was in on the gun theft, forcing him to go off on his own to bring the bad guys to justice. At the same time, dental supply salesman Andy Fiddler happens to be in Detroit for a business convention. During the course of investigating who is responsible for his partner's death, Derrick arrests Andy because of a miscommunication. Soon the hard-edged agent and the salesman have to team up to extricate themselves from their life-threatening predicament.